Extended half-life recombinant factor VIII treatment of hemophilia A in Brazil: an expert consensus statement - Margareth Castro Ozelo; Sandra Vallin Antunes; Paula Ribeiro Villaca; Luciana Correa Oliveira; Ieda Solange Pinto; Claúdia Santos Lorenzato; Alessandra Nunes Loureiro Prezotti; Renato Mantelli Picoli (Hematology, Transfusion and Cell Therapy, 2024)
Introduction: Treatment of hemophilia A in Brazil is offered to all patients at no cost. However, several unmet medical needs exist. Method: In this study, we applied the Delphi method to discuss with seven hemophilia A specialists the challenges that patients and the health system face regarding hemophilia A treatment and opportunities for improvement. Results: A consensus was obtained regarding the number of weekly infusions and patient adherence to treatment. The bleeding profile, unfavourable pharmacokinetics (PKs), low adherence and high daily activity were patient profiles that would benefit from using the extended half-life (EHL) recombinant factor VIII (rFVIII). The advantages of treatment with the EHL rFVIII were the lower number of infusions per week, which could increase patient adherence and decrease the risk of bleeds, due to a more constant plasma level, a lower value. Additionally, the EHL rFVIII could improve quality of life, especially in patients with high daily activity, such as adolescents and young adults. The panelists mentioned that EHL rFVIII, if available, could be offered first to the priority group (adolescents between 12 and 19 years old), followed by adults (20 to 64 years old) and elderly people (over 65 years old). Conclusion: In summary, the EHL rFVIII offers the optimal prophylaxis by decreasing the dose frequency, increasing the treatment adherence and improving the QoL, without compromising safety and efficacy.